2016
DOI: 10.1111/tpj.13226
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐level regulation of the chloroplast ATP synthase: the chloroplast NADPH thioredoxin reductase C (NTRC) is required for redox modulation specifically under low irradiance

Abstract: SUMMARYThe chloroplast ATP synthase is known to be regulated by redox modulation of a disulfide bridge on the c-subunit through the ferredoxin-thioredoxin regulatory system. We show that a second enzyme, the recently identified chloroplast NADPH thioredoxin reductase C (NTRC), plays a role specifically at low irradiance. Arabidopsis mutants lacking NTRC (ntrc) displayed a striking photosynthetic phenotype in which feedback regulation of the light reactions was strongly activated at low light, but returned to w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
97
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(105 citation statements)
references
References 59 publications
7
97
0
1
Order By: Relevance
“…In ntrc , high steady‐state pmf under low light intensity (Figures e, and a) was likely caused by impaired activation of the chloroplast ATP synthase and the Calvin–Benson cycle as previously reported (Carrillo et al., ; Nikkanen et al., ). Furthermore, exceptionally high NPQ was recorded in the ntrc line, especially at low light (Supporting Information ).…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…In ntrc , high steady‐state pmf under low light intensity (Figures e, and a) was likely caused by impaired activation of the chloroplast ATP synthase and the Calvin–Benson cycle as previously reported (Carrillo et al., ; Nikkanen et al., ). Furthermore, exceptionally high NPQ was recorded in the ntrc line, especially at low light (Supporting Information ).…”
Section: Resultssupporting
confidence: 78%
“…The ntrc knockout has a stunted and low chlorophyll phenotype, which is particularly severe in plants grown under short photoperiods (Lepistö et al., , ; Pérez‐Ruiz et al., ). The mutant suffers from an impaired ability to activate the ATP synthase and CBC enzymes as well as elevated nonphotochemical quenching (NPQ) (Carrillo, Froehlich, Cruz, Savage, & Kramer, ; Naranjo et al., ; Nikkanen, Toivola, & Rintamäki, ; Thormählen et al., ). In contrast, NTRC overexpression lines (OE‐NTRC), with 15–20 times higher NTRC content compared to WT, show wild‐type–like visible phenotype, enhanced vegetative growth, and increased activation of the ATP synthase and CBC enzymes, particularly in darkness and low light (Nikkanen et al., ; Toivola et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…4C). Previous reports have shown that the deficiency of NTRC causes the impairment of light utilization and slightly affects the redox state of the g-subunit of ATPase, hence affecting the qE component of NPQ (Carrillo et al, 2016;Naranjo et al, 2016b). Therefore, the combined deficiency of NTRC and f-or x-type Trxs affects the redox regulation of chloroplast metabolic pathways such as the CalvinBenson cycle but also the efficiency of light utilization, which ultimately might be the reason for the severe growth-retarded phenotype shown by the ntrc-trxx and ntrc-trxf1f2 mutants.…”
Section: Discussion Ntrc Acts In Concert With Different Types Of Trxsmentioning
confidence: 99%
“…It has long been known that the chloroplast ATP synthase is regulated by modulation of a cysteine pair located in a regulatory loop in γ-subunit (Ort and Oxborough, 1992), which is modulated by light-induced electron flow from PSI through thioredoxin at high light and the chloroplast NAD(P)H: thioredoxin reductase C (NTRC) at low light (Carrillo et al, 2016). This regulatory mode is proposed to prevent wasteful ATP hydrolysis in the dark (Wu et al, 2007).…”
Section: Introductionmentioning
confidence: 99%